Treatment Results and Prognostic Factors of Brain Metastases From Ovarian Cancer: A Single Institutional Experience of 56 Patients. Issue 8 (1st October 2018) - Kwon, Ji-Woong; Yoon, Joon Ho; Lim, Myong Cheol; Joo, Jungnam; Yoo, Heon; Shin, Sang-Hoon; Park, Sang Yoon; Lee, Sang Hyeon; Kim, Yeon-Joo; Kim, Joo-Young; Gwak, Ho-Shin
Abstract : Objectives: The most appropriate treatments for brain metastases from ovarian cancer have not been established mainly because of its rarity. The objective of this study was to describe clinical results of treatment and prognostic factors of patients with brain metastases from ovarian cancer treated at a single institution. Materials and Methods: We retrieved information from the electronic medical records of 56 consecutive patients (2.8%) with brain metastases, from a total of 2008 patients with ovarian cancer. Endpoints were the pattern of treatment failure, progression-free survival, and overall survival (OS). Results: Radiation was the most common initial treatment for brain metastases (59%), followed by surgery (23%). The median progression-free survival was 9.8 months. Radiological progression was confirmed in 20 patients: 7 had leptomeningeal carcinomatosis (37%), 8 had local recurrence, and 5 had distant recurrence. Median OS was 11.25 months, and the 1-year OS rate was 48.2%. Patients received surgery for single metastasis as initial treatment showed median OS of 24.1 months, which was significantly prolonged compared with the other patients ( P = 0.0002). Of the 48 patients who died, 29 (60%) died of systemic disease and 7 (15%) died of central nervous system progression. Karnofsky Performance Status greater than or equal to 70, control of systemic cancer, serous histology, and surgery for brain metastases were associated with improved OS in multivariable analysis ( P < 0.05). Conclusions: Surgical resection for single or symptomatic brain metastases from ovarian cancer prolonged OS significantly. Multimodality treatment, including control of systemic cancer, appeared to be an important factor in prolonging OS.